Different fibroblast subtypes propel spatially defined ileal inflammation through TNFR1 signalling in murine ileitis - Lida Iliopoulou; Christos Tzaferis; Alejandro Prados; Fani Roumelioti; Vasiliki Koliaraki; George Kollias (Nature Communications)
Abstract Crohn’s disease (CD) is a persistent inflammatory disorder primarily affecting the terminal ileum. The Tnf ΔΑRE mice, which spontaneously develop CD-like ileitis due to TNF overexpression, represent a faithful model of the human disease. Here, via single-cell RNA sequencing in Tnf ΔΑRE mice, we show that murine TNF-dependent ileitis is characterized by cell expansion in tertiary lymphoid organs (TLO), T cell effector reprogramming, and accumulation of activated macrophages in the submucosal granulomas. Within the stromal cell compartment, fibroblast subsets (telocytes, trophocytes, PdgfraloCd81− cells) are less abundant while lymphatic endothelial cells (LEC) and fibroblastic reticular cells (FRC) show relative expansion compared to the wild type. All three fibroblast subsets show strong pro-inflammatory signature. TNFR1 loss or gain of function experiments in specific fibroblast subsets suggest that the Tnf ΔΑRE-induced ileitis is initiated in the lamina propria via TNF pathway activation in villus-associated fibroblasts (telocytes and PdgfraloCd81− cells), which are responsible for the organization of TLOs. Trophocytes drive disease progression in the submucosal layer, accompanied by the excessive formation of granulomas. These findings provide evidence for spatial regulation of inflammation by fibroblast subsets and underscore the pivotal role of fibroblasts in the inception and advancement of ileitis.